Ireland's Women in Finance Charter: Annual Report 2024 - Hingre, Garance; Russell, Helen (ESRI, 2024)
Ireland’s Women in Finance Charter is an initiative to address gender imbalances in the sector, by supporting firms’ initiatives to improve their female representation. Created in 2022, the Charter now counts 81 signatories. Together these firms employ over 63,428 workers, representing just over half of employees in the sector. Therefore, the changes undertaken by the signatory firms have the potential to significantly influence the opportunities available to women working in the Irish financial sector. This is the second annual Ireland’s Women in Finance Charter report. It outlines the progress made by the 81 signatories and their employees.
Keywords: Ireland, Women in Finance